Surge Arresters Modeling for Electromagnetic Transient Analysis in Power Systems - Albuquerque, Feipe P.; Lourenco, Luis F. N.; Costa, Eduardo C. M.; Kurokawa, Sergio [UNESP]; IEEE (Ieee, 2017)
This paper presents a study of sensitivity of the equivalent circuit of ZnO surge arresters based on the model proposed by the IEEE. The main contribution of the proposed paper consists in some modifications in the fitting procedure of the equivalent LRC circuit of the surge arrester in order to improve the accuracy during electromagnetic transient simulations in power systems. The proposed equivalent circuit is modeled by using the Alternative Transient Program - ATP.
Keywords: surge arrester; electromagnetic transients; modeling; lightning